2014
DOI: 10.1096/fj.13-243139
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin modulates integrin function and mechanical activation in the cardiomyocyte

Abstract: β1 integrins (β1) transduce mechanical signals in many cells, including cardiac myocytes (CM). Given their close localization, as well as their role in mechanotransduction and signaling, we hypothesized that caveolin (Cav) proteins might regulate integrins in the CM. β1 localization, complex formation, activation state, and signaling were analyzed using wild-type, Cav3 knockout, and Cav3 CM-specific transgenic heart and myocyte samples. Studies were performed under basal and mechanically loaded conditions. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 58 publications
1
19
0
Order By: Relevance
“…Phosphorylation of caveolin-1 at Tyr14 is involved in the integrin-regulated caveolae trafficking and also in signaling at focal adhesions in migrating cells (31). ␤ 1 -Integrin is also an important component of caveolae membranes (28,16,40). In the present study, SW therapy enhanced protein levels of ␤ 1 -integrin, but not those of caveolin-1, and enhanced the phosphorylation state of caveolin-1 and ␤ 1 -integrin activity.…”
Section: Discussionsupporting
confidence: 48%
“…Phosphorylation of caveolin-1 at Tyr14 is involved in the integrin-regulated caveolae trafficking and also in signaling at focal adhesions in migrating cells (31). ␤ 1 -Integrin is also an important component of caveolae membranes (28,16,40). In the present study, SW therapy enhanced protein levels of ␤ 1 -integrin, but not those of caveolin-1, and enhanced the phosphorylation state of caveolin-1 and ␤ 1 -integrin activity.…”
Section: Discussionsupporting
confidence: 48%
“…To investigate whether loss of CM Tln2 and the subsequent compensatory increase in Tln1 expression causes changes in integrin activation, we stained heart tissue with the 9EG7 antibody that specifically recognizes the activated form of the β1-integrin subunit (26,27). Consistent with the reduction of total β1-integrin expression in CMs, the levels of activated β1 integrin detected by the 9EG7 antibody were also reduced in Tln2KO heart compared with WT.…”
Section: Integrins and Proteins Of The Integrin Complex Are Altered Imentioning
confidence: 88%
“…Integrin has been demonstrated to mediate mechanotransduction in various types of cells, including neurons, fibroblasts, epithelial cells, cardiomyocytes, and tendon stem/progenitor cells (Ye et al, 2010; Zhang et al, 2011; Moore et al, 2012; Fiore et al, 2015; Israeli-Rosenberg et al, 2015; Sun X. et al, 2016; Sun Z. et al, 2016; Wang et al, 2016). Recent studies have also shown that integrin plays a vital role in cell migration; the migration of SCs on astrocytes was shown to be clearly integrin-dependent (Nodari et al, 2007; Afshari et al, 2010).…”
Section: Introductionmentioning
confidence: 99%